1999
DOI: 10.1038/sj.bjc.6690662
|View full text |Cite
|
Sign up to set email alerts
|

p21/WAF1 expression in human colorectal carcinoma: association with p53, transcription factor AP-2 and prognosis

Abstract: p21/WAF1 expression was studied in a series of 162 colorectal carcinoma patients and its relation to p53- and activator protein (AP)-2 expressions and to stage as well as survival was assessed. p21 expression was moderate or intense in 33% of the tumours, and 53% of the tumours had moderate or strong p53 staining intensity. Eighty-nine percent of the tumours showed a weak cytoplasmic AP-2 signal. As expected, p21 and p53 stainings were inversely related to each other ( P < 0.001). There … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
48
2
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 36 publications
8
48
2
1
Order By: Relevance
“…Immunohistochemical studies have shown that downregulated cytoplasmic AP-2a expression was consistently seen in high grade and advanced Duke's stage tumors (Ropponen et al, 2001). In addition, low cytoplasmic AP-2a expression was seen in high-grade carcinomas (Ropponen et al, 2001), corroborating previous reports in which low AP-2a expression was associated with higher tumor malignancy and poor survival (Karjalainen et al, 1998;Ropponen et al, 1999;Pellikainen et al, 2003). However, the exact mechanism by which loss of AP-2a contributes to colon cancer progression is yet to be investigated.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…Immunohistochemical studies have shown that downregulated cytoplasmic AP-2a expression was consistently seen in high grade and advanced Duke's stage tumors (Ropponen et al, 2001). In addition, low cytoplasmic AP-2a expression was seen in high-grade carcinomas (Ropponen et al, 2001), corroborating previous reports in which low AP-2a expression was associated with higher tumor malignancy and poor survival (Karjalainen et al, 1998;Ropponen et al, 1999;Pellikainen et al, 2003). However, the exact mechanism by which loss of AP-2a contributes to colon cancer progression is yet to be investigated.…”
Section: Introductionsupporting
confidence: 87%
“…AP-2 is one of the critical factors of neural gene expression (Mitchell et al, 1991) and various neural genes contain AP-2 binding sites in their regulatory regions. Loss of AP-2a expression has been associated with progression of melanoma , prostate cancer (Ruiz et al, 2004) and colorectal cancer (Ropponen et al, 1999(Ropponen et al, , 2001). In addition, immunohistochemical studies of human melanoma, breast and colorectal cancer specimens have revealed that loss of AP-2a coincides with poor prognosis (Karjalainen et al, 1998;Ropponen et al, 1999;Pellikainen et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In clinical specimens of invasive breast cancer, a correlation between low AP-2 expression and disease progression was demonstrated, suggesting a tumor suppressor-like role for AP-2 (Gee et al, 1999). In colorectal carcinoma, AP-2 expression correlates with p21/WAF1 expression and recurrence-free survival (Ropponen et al, 1999). These observations indicate that AP-2 plays multiple roles in both normal development and the development/ progression of cancer.…”
mentioning
confidence: 67%
“…Increased p21 expression has also been seen in several types of malignant tumors (Baekelandt et al, 1999;Barboule et al, 1998), and a higher level of p21 has been correlated with higher 5-year survival rate (Kuwahara et al, 1999;Natsugoe et al, 1999;Ropponen et al, 1999). To evaluate p15 PAF 's potential function in tumor development, p15 PAF expression level was measured using tumor blots (Invitrogen).…”
Section: P15 Paf Expression Is Increased In Tumor Tissuesmentioning
confidence: 99%